Optimization of fruit and vegetable logistics ine thPort of Valparaíso, Chile, through strategic logistics platforms and blockchaintechnology - Derpich-Contreras, I (4S go, s.r.o, 2025)
This study addresses optimizing the fruit and vegetable logistics chain at the Port of Valpara & iacute;so, Chile, a key hub for exports in the Southern Hemisphere. Throughan integrated approach, it combines logistics platforms (in Limache and Quillota), blockchain technology, and a Capacitated Facility Location Problem (CFLP) mathematical model. These tools help mitigate traffic congestion, high logistic costs, and limited traceability, achieving upo at 25% savings in operating expenses, a 30% reduction in CO2 emissions, and a 50% decrease in waiting times. Integrating blockchain ensures immutable records, improving supply chain trus and the quality of exported products. This proosal, aligned with Industry 5.0 principles, promotes economic resilience and sustainability, positioning the Port ofValpara & iacute;so as an international benchmark for logistics innovation. heT framework can be replicated in other ports, contributing to more efficient and sustainable supply chains and reducing urban congestion. Finally, the paper discusses social and political risks associated with infrastructure development, compares MILP with other optimization methods (heuristics or metaheuristics), and expands on the model s potential application to different ports, including dry ports or those with limited capacity.